2014
DOI: 10.1039/c4nr04783d
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-doped porous reduced graphene oxide hollow nanosphere frameworks as metal-free electrocatalysts for oxygen reduction reaction and as supercapacitor electrode materials

Abstract: Chemical doping with foreign atoms is an effective approach to significantly enhance the electrochemical performance of the carbon materials. Herein, sulfur-doped three-dimensional (3D) porous reduced graphene oxide (RGO) hollow nanosphere frameworks (S-PGHS) are fabricated by directly annealing graphene oxide (GO)-encapsulated amino-modified SiO2 nanoparticles with dibenzyl disulfide (DBDS), followed by hydrofluoric acid etching. The XPS and Raman spectra confirmed that sulfur atoms were successfully introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(98 citation statements)
references
References 48 publications
1
97
0
Order By: Relevance
“…Then NH2-SiO2/GO was pyrolyzed under an inert atmosphere and the subsequent elimination of the NH2-SiO2 template leaded to porous graphene [35]. It is thought that this kind of scenario may have led the porous structure.…”
Section: Characterization Of the Cuo/prgo Nanocompositementioning
confidence: 99%
See 1 more Smart Citation
“…Then NH2-SiO2/GO was pyrolyzed under an inert atmosphere and the subsequent elimination of the NH2-SiO2 template leaded to porous graphene [35]. It is thought that this kind of scenario may have led the porous structure.…”
Section: Characterization Of the Cuo/prgo Nanocompositementioning
confidence: 99%
“…Besides, the characteristic peak of GO at 10.4° in the XRD pattern disappeared, which indicates that GO has been reduced effectively during the synthesis process. The peaks at35.60°, 38.73°, 48.90°, 58.3°, 61.5° and 68.1° suggest the formation of CuO (JCPDS 48-1548). Compared with the reference card statistics of CuO, no other reflections for Cu metal or other copper-compound were observed.…”
mentioning
confidence: 96%
“…On the other hand, the heteroatoms, such as nitrogen and sulfur, have been introduced into carbon materials in order to further improve electrochemical performance of carbon electrodes [21][22][23]. Nitrogen-containing carbon materials can be prepared by the carbonization of nitrogen-enriched polymers and materials, such as polyaniline, melamine, polypyrrole and so on [24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to combining the graphene film with pseudocapacitive materials at the nanoscale, direct doping of heteroatoms into carbon scaffolds also increases the pseudocapacitance [109][110][111]. It has been shown that C-S bonds near edges or defects are active sites which influence the charging of the electrical double layer and facilitate the pseudocapacitive behavior [112]. Therefore, a bottom-up method has been developed to synthesize sulfur doped graphene (SG) films .…”
Section: Graphene Filmsmentioning
confidence: 99%